PENGEMBANGAN MODUL MENULIS TEKS TANGGAPAN DESKRIPTIF BERBASIS MASALAH DI SEKOLAH MENENGAH PERTAMA - Ade Putra (Institut Pendidikan Tapanuli Selatan, 2022)
This research is motivated by the low learning outcomes of students because students only learn to use source books provided by the government as learning materials as a result of which learning is not optimal. The results of observations and interviews in Indonesian language learning in writing descriptive response texts in grade IV that are less than optimal. The purpose of this study was to produce teaching materials in the form of a problem-based learning writing module in Indonesian language learning in writing descriptive response texts that were valid for use by grade VII junior high school students. The research subjects were thirty-one grade VII students of SMP Negeri 12 Padang. This research is a development research using a 4D development model. Development begins with the stage of defining, designing, ending with development. The research data in the form of quantitative were obtained from the expert and practitioner validators, teachers and students, student learning outcomes. Based on the data analysis and discussion, it can be concluded that the validity of the Problem-Based Learning module on the descriptive response text writing material developed is very valid, with a percentage of 92.50%.